E-LEARNING PEDAGOGICAL CHALLENGES OF EFL TEACHERS DURING COVID-19 PANDEMIC - Putri, Wulandari (Prodi Teknologi Pendidikan, 2021)
The COVID-19 outbreak enforced teachers to shift a face to face learning into virtual learning, widely known as E-Learning, hastily. The problems and challenges might arise due to the quick shift of learning format. Therefore, this study was aimed at investigating the challenges faced by primary and secondary EFL teachers in conducting online English learning during this pandemic. The qualitative method was used by involving three teachers representing each level of education, including primary level and secondary level. The teachers were chosen purposively by considering various criteria. An open-ended questionnaire was distributed through a Google form. The data were then analyzed inductively. Findings show that productive skills, including speaking and writing skills, become the most challenging skills to teach. Moreover, giving feedback and teaching difficult materials in the basic competence also become the challenges in conducting e-learning for EFL teachers. Therefore, a training specifically provides an effective strategy and approach in online environment is required.Wabah COVID-19 memaksa para guru untuk mengubah pembelajaran tatap muka menjadi pembelajaran virtual, yang dikenal sebagai E-Learning, dengan tergesa-gesa. Masalah dan tantangan mungkin muncul karena pergeseran format pembelajaran yang cepat. Oleh karena itu, penelitian ini bertujuan untuk menyelidiki tantangan yang dihadapi oleh guru EFL sekolah dasar dan menengah dalam melakukan pembelajaran bahasa Inggris daring selama pandemi ini. Metode kualitatif digunakan dengan melibatkan tiga orang guru yang mewakili setiap jenjang pendidikan, yaitu jenjang SD, SMP, dan SMK. Para guru dipilih dengan melalui purposive sampling dengan mempertimbangkan berbagai kriteria. Kuesioner terbuka dibagikan melalui formulir Google. Data tersebut kemudian dianalisis secara induktif. Temuan menunjukkan bahwa keterampilan produktif, termasuk keterampilan berbicara dan menulis, menjadi keterampilan yang paling menantang untuk diajarkan. Selain itu, memberikan umpan balik dan materi yang sulit dalam kompetensi dasar juga menjadi tantangan dalam melakukan e-learning bagi guru EFL. Oleh karena itu, diperlukan pelatihan yang secara khusus memberikan strategi dan pendekatan yang efektif dalam lingkungan online.